STRATEGI GURU PENDIDIKAN AGAMA ISLAM PADA PROSES PEMBELAJARAN DALAM JARINGAN (DARING) - Kusdani Kusdani (Pendidikan Agama Islam Institut Agama Islam Diniyyah Pekanbaru, 2021)
The online learning process carried out by all levels of education at this time requires all teachers to have an appropriate strategy so that the material presented is easily understood by students and students have high learning motivation. PAI teachers are no exception, PAI teachers are also required to have a strategy in this online learning process. Based on initial observations, there are various strategies used by PAI teachers during the online learning process. Departing from this, this research wants to see more specifically which strategy is the most dominantly used by PAI teachers during the online learning process. This research is a qualitative research which analyzed using Miles and Huberman model. The sample of this study amounted to five PAI teachers. Methods of data collection using the method of observation and documents. The results showed that PAI teachers were more dominant in using the WhatsApp platform and Zoom Cloud Meeting when the online learning process was carried out.